Fenomena Langgam Penjor Galungan pada Era Kekinian Bali - I Wayan Mudra (Jurnal Kajian Bali (Journal of Bali Studies), 2018)
The making of penjor for the Hindu holy day of Galungan shows the existence of innovation and excessive creativities. This research was aimed at investigating the phenomenon of penjor Galungan style in the contemporary Bali which viewed from the community involvement, the use of material, and the emergence of spiritual meaning. This study used descriptive qualitative research method. The data collection was carried out through observation and literature review. The analysis shows that the Hindu community in Bali currently prefers buying the elements of penjor for rather than make by themselves; the making of penjor Galungan uses contemporary available material; and the structural spiritual meaning of penjor Galungan is being embellished by the domination of contemporary spiritual meanings.